APA YANG TIDAK BOLEH KITA LUPAKAN (Memori dalam Tradisi Lisan Massomba Tedong) - Susia Imanuella (Pangadereng : Jurnal Hasil Penelitian Ilmu Sosial dan Humaniora, 2020)
ABSTRACTAs one manifestation of intangible cultural heritage, the oral tradition that preserves various kind of human experiences does not only exist as narratives of events in the past, but in the form of traditional ceremonies, oral traditions become a representation of the past which cannot be separated from the situation and conditions today, when this tradition is spoken. The oral tradition of massomba tedong, which became a part of Tongkonan consecration ceremonies in Toraja has a crucial meaning for the Torajans' life. Not only to recall the memory regarding their origin and identity as a group of indigenous peoples, but the tradition of massomba tedong is also presented to strengthen the "role" of certain groups in the traditional order through various elements which are shown in the narrative. Through the ethnographic methods, the oral tradition of massomba tedong is recognized not only as a part that fulfills the consecration ceremony of the Tongkonan, more than that this tradition becomes the living space of the Toraja indigenous people to recall memories about their cultural identity as heirs of the great tradition.Keywords: Oral tradition, oral narrative, Massomba tedong, Cultural memory, The Torajans